El liderazgo del cambio organizacional (2018)
This article makes a short description of the administrative thinking evolution, to show that in some cases, the estrategies of change are focused specially in the human dimension, whereas in other cases, the technical variables are emphizised. The programmes of change that are oriented towards psychosocial aspects of the organization, aim for the modification of the people’s attitude and behaviour, in order to improve the total productivity and efficiency of the company. On the other hand, the strategy focused on the technic aspects, has as main purpose to change the struc-ture, processes and the technology, with the expectation that later the people will adapt to the new conditions or they will be replaced by new employees. Each one of the approaches requires a particular type of lidership and has a representative model. The human emphasis requires a par-ticipative lidership and its paradigm of reference is the organizational development. Differently, the thechnical emphasis generally finds itself bound to an authoritarian lidership and its model of reference is the Re-ingeneering. Finally, the content of the article relates to the situational lider-ship, but it is indicated that the most relevant element of the situation is the degree of structure of the problems.